Efficacy of biocontrol agents in suppressing Fusarium oxysporum f. sp. cubense TR4, the causal pathogen of Fusarium wilt of banana in Bihar - Manoj , K P; Singh, S K; Aman, Jaiswal; Dilip, K C; Anamita, Sen; Piyush, Kumar; Swati, Chandra; Piyush, Parihar; Wongamthing, R; Shaik, Asif Basha; et al. (Plant Science Today, 2026)
The present study was conducted at the Department of Plant Pathology and Nematology, RPCAU, Pusa, during the year 2022–2023. It demonstrates the in vitro antagonistic effect of native Trichoderma isolates and fungal endophytes, as well as the inhibitory effects of volatile organic compounds (VOCs) from four selected bacterial endophytes against Fusarium oxysporum f. sp. cubense (Foc TR4). The results revealed that Trichoderma isolates, i.e. T1-1723; T2-1723; T3-1723, in which T-3-1723 and Trichoderma asperellum showed maximum per cent mycelium inhibition of 88.89 and 88.92 respectively, whereas fungal endophytes LfFE1 exhibited inhibition per cent of 44.78 %. In addition, bacterial endophytes (GNBEF-14) have shown an inhibition of 40.13 % over control. Overall, it was found that among all biocontrol agents, only Trichoderma isolates showed best antagonistic effect against pathogen. Thus, it can be used further to test their efficacy and develop consortia to manage this devastating pathogen at the field level.